Fatal Rupture of Occult Posttraumatic Left Ventricular Aneurysm in a Child - Morten Engholm, MD, PhD; René F. Andersen, MD, PhD; Maiken K. Larsen, MD, PhD; Lars Jakobsen, MD, PhD; Jesper V. Bjerre, MD (JACC: Case Reports, 2023)
Left ventricular aneurysm is a potentially serious but rare condition in children. This case describes delayed but fatal rupture of an occult posttraumatic left ventricular aneurysm in an 11-year-old boy with a history of blunt chest trauma from a high-impact automobile collision 7 months earlier. (Level of Difficulty: Intermediate.)